Interpretasi Biomarker dan Korelasi Minyak-Batuan Induk pada Sumur TNG-1, Cekungan Sumatra Tengah - Putri Dwi Afifah; Muhammad Agni Gustama; Sri Desdita Komari; Lusitania; Aisyah Minzikrina Masbar Rus; Widi Atmoko (Mataram University, 2026)
This study interprets biomarker characteristics and evaluates the genetic relationship between oil samples and potential source rocks from the TNG-1 well in the Cekungan Sumatra Tengah. The analysis was conducted using oil and rock geochemical parameters, n-alkane chromatograms, terpene and sterane distributions, as well as sterane ternary plots (C₂₇–C₂₈–C₂₉). The results indicate that oil samples at intervals of 5238–5277 ft, 5246–5248 ft, and 5266–5268 ft exhibit consistent geochemical characteristics and suggest thermal maturity within the early to mid-mature oil window. In contrast, rock samples at intervals of 4814 ft, 5046 ft, and 5151 ft show immature characteristics, indicated by CPI > 1.0, high Pr/nC₁₇ ratios, and n-alkane distributions biased toward long-chain compounds. Biomarker analysis reveals similarities in n-alkane distribution patterns, isoprenoid ratios, and C₂₇–C₂₈–C₂₉ sterane compositions between oil and source rock samples, indicating a strong genetic relationship. Sterane compositional correlation suggests that most samples, both oil and rock, originated from shallow lacustrine to estuarine depositional environments with significant higher-plant input. Overall, the oil samples show a strong correlation with the source rock at the 5151 ft interval based on the consistency of n-alkane, hopane, and sterane patterns.